Global rebalancing in the internet age : impact on society, government & business - Yang Razali Kassim (2012)
The Second Singapore Global Dialogue saw a heated debate over issues relating to the changing world order. Can there be an Asian response to the search for global governance and innovative solutions to the common challenges of humanity?